The Pivotal Role of Regulatory T Cells in the Regulation of Innate Immune Cells - Okeke, Emeka B.; Uzonna, Jude E. (Frontiers in Immunology, 2019)
The distinction between innate and adaptive immunity is one of the basic tenets of immunology. The co-operation between these two arms of the immune system is a major determinant of the resistance or susceptibility of the host following pathogen invasion. Hence, this interactive co-operation between cells of the innate and adaptive immunity is of significant interest to immunologists. The sub-population of CD4+ T cells with regulatory phenotype (regulatory T cells; Tregs), which constitute a part of the adaptive immune system, have been widely implicated in the regulation of the immune system and maintenance of immune homeostasis. In the last two decades, there has been an explosion in research describing the role of Tregs and their relevance in several immunopathologies ranging from inflammation to cancer. The majority of these studies focus on the role of Tregs on the cells of the adaptive immune system. Recently, there is significant interest in the role of Tregs on cells of the innate immune system. In this review, we examine the literature on the role of Tregs in immunology. Specifically, we focus on the emerging knowledge of Treg interaction with dendritic cells, macrophages, neutrophils, and γδ T cells. We highlight this interaction as an important link between innate and adaptive immune systems which also indicate the far-reaching role of Tregs in the regulation of immune responses and maintenance of self-tolerance and immune homeostasis.